The good neighbor cookbook : 125 easy and delicious recipes to surprise and satisfy the new moms, new neighbors, recuperating friends, community-meeting members, book club cohorts, and block party pals in your life! - Quessenberry, Sara (Andrews McMeel Pub., 2011)
Provides 125 recipes for appetizers, soups, salads, entrées, and snacks suitable for a variety of gatherings, including block parties, potluck dinners, book clubs, and recuperating friends.